Microwave and ultrasound pre-treatments to enhance anthocyanins extraction from different wine lees. (30th January 2019) - Romero-Díez, R.; Matos, M.; Rodrigues, L.; Bronze, Maria R.; Rodríguez-Rojo, S.; Cocero, M.J.; Matias, A.A.
Highlights: Wine lees present higher anthocyanin concentrations than grape marc. Microwave pre-treatment enhance anthocyanin extraction up to two fold. Microwave pre-treatment reduce the extraction time from 15 min to 90 s. Ultrasounds only affect the extraction time, decreasing it from 15 min to 5 min. ORAC values increase with the employment of the pre-treatments. Abstract: Wine lees are rich in anthocyanins (AC), natural colorants with health promoting properties. The extraction kinetics of AC from different wine lees in conventional solid–liquid extraction were studied for the first time. The influence of parameters such as temperature, solid–liquid ratio (RS-L ) and type of solvent (hydro-alcoholic mixtures) was also studied. Furthermore, microwaves (MW) and ultrasounds (US) were used as pre-treatments (a prior step to the conventional extraction) in order to increase AC yield. Maximum extraction yield (2.78 mgMALVIDIN-EQUIVALENTS /gDRY-LEES ) was achieved after 15 min at 25 °C, with a RS-L of 1/10 (g/mL) and with a 50%vol. ethanol mixture. When MW were used AC extraction yield was doubled (6.20 mgMALVIDIN-EQUIVALENTS /gDRY-LEES ) and the required time to achieve a constant yield was reduced (from 15 min to 90 s). Meanwhile, US only shortened extraction time in less proportion (from 15 to 5 min). Putative identification of main extract compounds was performed by LC/MS-MS.